The other in text, the other in politics – Gadamer and Derrida - Dadlez, Jakub (Hybris, 2017)
In this article I compare Hans-Georg Gadamer’s philosophical hermeneutics and Jacques Derrida’s deconstruction. I try to demonstrate the similarities (focus on language and history), but moreover the differences between them. The core issue is the problem of the other, which appears in the works of both authors. Two perspectives are applied: concerning the notion of text (or tradition), and referring to the field of the political. Gadamer strives to communicate with the other (text) in the mutual understanding, although he has no hope in finding a final sensus communis. Derrida emphasizes the difference underlying every thought, as well as situations of understanding as such. As a result, their visions of democracy differ – subtly, but essentially.